EXPLORING THE KNOWLEDGE AND ATTITUDES OF PEOPLE TOWARDS MILLETS ON FOOD PLATE (International Journal of Food and Nutritional Sciences, 2022)
Millets are a group of small-seeded grasses that have been cultivated for thousands of years in various parts of the world, including Africa, Asia, and Europe. Millets are known for their high nutritional value and are an important source of dietary fiber, minerals, and vitamins. However, the consumption of millets has declined over the years due to various reasons, such as urbanization, industrialization, and the availability of alternative food options. This research paper aims to review the knowledge, and attitudes of people towards millets on food plate, including their perception, knowledge, consumption, and factors influencing their attitudes.Keeping above view in mind a survey was carried out on 120 people to know the knowledge and attitude regarding health benefits of millets and millet recipes. The result shows that almost everyone knows that the year is celebrated as IYOM (International year of Millets), but the knowledge about health benefits and recipes are not known to them, so, there is a need to organise recipe workshops and demonstrations at all levels; educational institutions, offices, anaganwadi, hospitals, clubs, societies, supermarkets , so that our traditional knowledge will be transfer to upcoming generation, even millets can be replace in school lunch program to improve health status of children .